Murder at Dawn - Johnson, Tayo (Spectrum Books Limited, 1981)
This book is the first dramatic book in an exciting and fascinating new series featuring 3 officers of the Panti Street C.I.D renowned for their incredibly high success in the fight against crime and corruption in the city of Lagos.
Keywords: Fiction; Juvenile Literature